(3JaSjQ ShQI GdMOjOs - (3GdTjQGRj, GdbhGej, GdeqdG, UOQ GdOjf, eMeO Hf EHQGgje Hf jMji, J (B1059 (3g`s ((3YHO GdMSjf Hf QHjY GdCUagGfjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CaGV Ydi bdhH ChdjGFg (B...(3ChUjce CjgG GdHGMKjf Yf ObGFb eYQaI Gddg hedchJg HbhI GdJacQ hGdGfJbGd (B... (3Cf fbUO hGLO GdedchJ hjWjQhG SeGA bOS Gddg (B..(3Ydjce HLHd GdbQBf (B..s
(3BNQgG (B:s
.. (3hJQaY MGd GdLgdI GdCRhGd hJUOQge Ydi GdCNjGQ hGdCTQGa hNdh GdHbGY hGdHdGO Yef jYQa bOQ GdeYGQa hGdCSQGQ GdaGFVI Ydi bdhH GdYHGO aj NHGjG Ydhe GdeHJOC (B.. (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B5/ 303s
(3GdPQjYI (B4\1457s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs